Vertical distribution of blue Shark (Prionace glauca) in The Indian Ocean - Rochman Fathur (EDP Sciences, 2021)
Each fish species tends to choose a suitable environment suitable for its survival and reproduction horizontally and vertically. Blue shark (Prionace glauca) is the dominant catch of pelagic sharks by-catch in the Eastern Indian Ocean longline tuna fishery, with about 70% of the total sharks caught in this fisheries. This study aims to provide the information and the vertical analysis distribution of blue sharks based on temperature and depth in the Indian Ocean. The scientific observer collected 2,951 set-by-set longline fishing data based on Research Institute For Tuna Fisheries (RITF) from January 2006 to December 2018, on which the present analysis was made. The mini logger was used to measure the vertical distribution of blue sharks in the longline fisheries. This result indicated that blue shark was caught between 75.18-445.46 m depth, with 84% of which live at thermocline area (70-300 m depth), and 16% lived in underlayer area (>300 m depth). Blue sharks distributed in the underlayer area have a larger body size than those in the thermocline area with a size >180 cmFL compared to 50-170 cmFL in the thermocline area.